Classification of ventricular septal defects. - Soto, B (1980)
A classification with clinical significance is proposed for ventricular septal defect based on the study of 220 hearts with defects of the ventricular septum. All had atrioventricular and ventriculoarterial concordance with normal relations of cardiac structure. For the purpose of classification, the ventricular septum was considered as possessing muscular and membranous portions, the muscular septum itself being divided into inlet, trabecular, and outlet (or infundibular) components. Defects were observed in the area of the membranous septum, termed perimembranous defects; within the muscular septum, termed muscular defects; or in the area of septum subjacent to the arterial valves, termed subarterial infundibular defects. Perimembranous defects were found extending either into the inlet, trabecular, or infundibular septa. Muscular defects were found in or between the inlet septum, trabecular septum, or infundibular septum. Review of the angiograms showed that the classification was easy to use in the catheterisation laboratory, and our observations suggest that the precision thus obtained has considerable surgical significance.